Pituitary gland volumes in bipolar disorder. - Clark, I; Mackay, C; Goodwin, G (Elsevier, 2014)
BACKGROUND: Bipolar disorder has been associated with increased Hypothalamic-Pituitary-Adrenal axis function. The mechanism is not well understood, but there may be associated increases in pituitary gland volume (PGV) and these small increases may be functionally significant. However, research investigating PGV in bipolar disorder reports mixed results. The aim of the current study was twofold. First, to assess PGV in two novel samples of patients with bipolar disorder and matched healthy controls. Second, to perform a meta-analysis comparing PGV across a larger sample of patients and matched controls. METHODS: Sample 1 consisted of 23 established patients and 32 matched controls. Sample 2 consisted of 39 medication-naïve patients and 42 matched controls. PGV was measured on structural MRI scans. Seven further studies were identified comparing PGV between patients and matched controls (total n; 244 patients, 308 controls). RESULTS: Both novel samples showed a small (approximately 20mm(3) or 4%), but non-significant, increase in PGV in patients. Combining the two novel samples showed a significant association of age and PGV. Meta-analysis showed a trend towards a larger pituitary gland in patients (effect size: .23, CI: -.14, .59). LIMITATIONS: While results suggest a possible small difference in pituitary gland volume between patients and matched controls, larger mega-analyses with sample sizes greater even than those used in the current meta-analysis are still required. CONCLUSIONS: There is a small but potentially functionally significant increase in PGV in patients with bipolar disorder compared to controls. Results demonstrate the difficulty of finding potentially important but small effects in functional brain disorders.